Connection of coupled buildings: A state-of-the-art review. (October 2021) - Doroudi, Rouzbeh; Hosseini Lavassani, Seyed Hossein
Abstract: This paper presents a state-of-the-art review of significant studies published on coupled buildings. The approach of connecting two adjacent buildings has been effectively applied to reduce structural responses of a coupled building which is subjected to seismic excitation. The coupled building control utilizes two adjacent structures to transfer dynamic force which is applied to each other in order to reduce critical responses. The aim of this article is to review technologies and methods in structural connection of coupled buildings which are classified as (a) rigid (b) passive, (c) semi- active, (d) active, and (e) hybrid. The concepts of these connections are explained and formulated. The comparison, application and feature of connections are tabulated. Finally, some approaches to enhance the performance of connections and draw backs of studies are suggested.